Pengaruh Penambahan Biodiesel Pada Pertamina Dex Terhadap Nilai Konsumsi Bahan Bakar Spesifik Mesin Genset Diesel 3000 Watt - Munthe, Dino Suryadi; Kusuma, I Gusti Bagus Wijaya; Astawa, Ketut (Teknik Desain Mekanika; Vol 14 No 1 (2025): Januari 2025 : Teknik Desain Mekanika, 2025)
Abstract The use of technology in today's era requires an energy source for its operation, one of which is petroleum. Diesel fuel or better known as diesel in Indonesia is classified as the most widely used fuel. The importance of the existence of diesel fuel and the depletion of petroleum supplies, the Indonesian government has taken action by utilizing biofuel or biodiesel mixed with diesel. This study was conducted with the aim of analyzing the effect of adding biodiesel fuel with Pertamina dex on changes in the specific consumption value of 3000 Watt diesel generator engines. This study uses an experimental method in the form of testing and analyzing physical characteristics on fuel variations and the effect of adding biodiesel to Pertamina Dex on the performance of diesel generator engines, namely the power produced, fuel consumption per second, and specific fuel consumption. The variations of biodiesel added used are B5, B10, B15, B20, B25, B30, B35, B40, B45, and B50 as well as dexlite as a comparator. The results of the study on the variation of biodiesel addition in Pertamina dex, B5 produced the lowest fuel consumption value of 0.181 Kg/kWh at 3000 Watt loading and B50 produced the highest value of 0.205 Kg/kWh at 3000 Watt loading. Each variation of the addition of biodiesel to Pertamina dex from five percent to fifty percent has experienced an increase in the value of specific fuel consumption. The addition of biodiesel to Pertamina dex increases the fuel density value. Changes in fuel density increase flash point and fire point so that the combustion process in diesel generator engines slows down. Specific fuel consumption in diesel generator engines is increasing as the amount of biodiesel used increases. Keywords: Specific fuel consumption, biodiesel, used cooking oil, diesel generator engine